ANALYSIS OF STUDENTS' ABILITY TO USE THE MATHEMATICAL INDUCTION PROOF METHOD IN CLASS XI SMK NEGERI 1 O’O’U - Buulolo, Erlina (Afore : Jurnal Pendidikan Matematika, 2024)
The purpose of this research is to describe students' abilities in using mathematical induction in Class XI at SMK Negeri 1 O’o’u. This study employs a qualitative approach with a descriptive method. The subjects of this research are 35 students from Class XI SMK Negeri 1 O’o’u. Data were analyzed through steps including data reduction, data presentation, and conclusion drawing. The data collection techniques used were tests and interviews. The results show that out of 35 students, 2 students fall into the very good category, 11 students into the good category, 9 students into the sufficient category, 6 students into the poor category, and 7 students into the very poor category. Thus, it can be concluded that students' ability to use the mathematical induction proof method is categorized as good, with a percentage of 31.42%. Based on these findings, the researcher suggests that students should deepen their understanding of the proof method and practice mathematical induction problems intensively, enabling them to solve various mathematical induction problems accurately.